If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 + x = 9 + 8x Solving 44 + x = 9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 44 + x + -8x = 9 + 8x + -8x Combine like terms: x + -8x = -7x 44 + -7x = 9 + 8x + -8x Combine like terms: 8x + -8x = 0 44 + -7x = 9 + 0 44 + -7x = 9 Add '-44' to each side of the equation. 44 + -44 + -7x = 9 + -44 Combine like terms: 44 + -44 = 0 0 + -7x = 9 + -44 -7x = 9 + -44 Combine like terms: 9 + -44 = -35 -7x = -35 Divide each side by '-7'. x = 5 Simplifying x = 5
| x+7/2=-30 | | 14-7x=90-21x | | 1/8/1/2= | | 9x+5-8x=11 | | 390=z+195+3.3y | | y=1/7x+2 | | 4/3(5/4p+1)+9/2p | | a^2*x^2+c^2=0 | | -(3xy-8)+2(3xy+6)= | | 4(-2x+3)=-5x | | 1/2(v+3/2)-2v | | -2.25=m+13.75 | | 1/2(61/9v-13/6) | | .4(4x+7)=2(3-3x)+12 | | n-7=-13.75 | | x-2=3x-4+5 | | -(3xy-9)+3(3xy+5)= | | -9/4(-7/3p+9/2) | | x^2+4x+11=x^2+3x+11 | | -8b+9+6b=-36+14 | | 7x-7=7(x+7) | | (20-2x)(16-2x)=0 | | x+7.5=-2 | | m+(-16)=-12 | | 6(d-3)+5= | | 3(15b-7)=3b-9 | | 5-v=34 | | n-(-2)=-13 | | 3n-5=2/3 | | 2x^2-3x-5=-2x^2+x+3 | | .25(x+2)=3x-6(2-x)-5 | | 16/9=-4t/7 |